Respuesta :
The answer is 1 3 3 1
The coefficients of the expanded terms are a combination; 4C1 , 4C2, 4C3, 4C4 multiplied by the x, y coefficients in the parenthesis. Since x, y coefficients in parenthesis is 1 the expanded coefficients are just the combinations.
4C1 = 1
4C2 = 3
4C3 = 3
4C4 = 1
[tex] (x+y)^{3} = 1*x^{3} y^{0} + 3*x^{2} y^{1} + 3*x^{1} y^{2} + 1*x^{0} y^{3} [/tex]
The coefficients of the expanded terms are a combination; 4C1 , 4C2, 4C3, 4C4 multiplied by the x, y coefficients in the parenthesis. Since x, y coefficients in parenthesis is 1 the expanded coefficients are just the combinations.
4C1 = 1
4C2 = 3
4C3 = 3
4C4 = 1
[tex] (x+y)^{3} = 1*x^{3} y^{0} + 3*x^{2} y^{1} + 3*x^{1} y^{2} + 1*x^{0} y^{3} [/tex]